2015
DOI: 10.9734/ejnfs/2015/20948
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Compliance Study of Food Fortification in Nigeria and Implications on Regulatory Monitoring

Abstract: Objectives:The aim of this study was to: 1) ascertain the levels of compliance with national fortification standards for vitamin A and iron; and 2) use the results as an advocacy tool to improve compliance and regulatory monitoring. Methods: The study was carried out in 2012 using quantitative devices (BioAnalyt iCheck Ex-Flouro, Ex-Chroma and Ex-Iron) for the measurement of vitamin A and iron in sugar, vegetable oil and flour. Laboratory analyses were also carried out using high performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Similarly, a national survey conducted in Nigeria revealed significant low levels of compliance for iron (1.0–21.0%) and vitamin A (12.2–33.3%) in wheat and maize flour (Ogunmoyela et al , 2013). Furthermore, similar trends were observed in the subsequent survey, where, only 16.7, 11.6 and 28% of sugar, vegetable oil and cereal flours, respectively, met the minimum fortification levels for vitamin A and iron (Ogunmoyela et al , 2015).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, a national survey conducted in Nigeria revealed significant low levels of compliance for iron (1.0–21.0%) and vitamin A (12.2–33.3%) in wheat and maize flour (Ogunmoyela et al , 2013). Furthermore, similar trends were observed in the subsequent survey, where, only 16.7, 11.6 and 28% of sugar, vegetable oil and cereal flours, respectively, met the minimum fortification levels for vitamin A and iron (Ogunmoyela et al , 2015).…”
Section: Discussionsupporting
confidence: 73%
“…Their assessment showed that 67, 89, 46, 86 and 80% of the salt, sugar, oil, wheat flour and semolina flour brands, respectively, were fortified. This was a notable improvement from the 2015 survey data (Ogunmoyela et al , 2015), demonstrating higher compliance with fortification standards than in the present study, with the exception of iron fortification in wheat (83 %) and maize flour (80%). Similar improvements have been reported in Uzbekistan, Morocco and Vietnam (Wirth et al , 2012).…”
Section: Discussionsupporting
confidence: 50%
“…Similarly, a national survey in Nigeria to determine the levels of Fe and vitamin A in common foods like maize and wheat flours, and condiments such as sugar and vegetable oils showed that the compliance for Fe and vitamin A fortification in flours were only 1% to 21% and 12% to 33%, respectively (Ogunmoyela et al, 2013). Similar trends were reported in a follow-up survey in the country where only approximately 17%, 12% and 28% of sugar, vegetable oil and cereal flours respectively met the minimum fortification standards for vitamin A and Fe (Ogunmoyela et al, 2015).…”
Section: Inadequate Food Fortificationsupporting
confidence: 69%
“…A similar national survey conducted in Nigeria also revealed significant low levels of compliance for Fe (1.0% -21.0%) and vitamin A (12.2% -33.3%) in wheat and maize flour (Ogunmoyela et al, 2013). Furthermore, similar trends were observed in the subsequent survey, where, only 16.7%, 11.6% and 28% of sugar, vegetable oils and cereal flours, respectively, met the minimum fortification levels for vitamin A and Fe (Ogunmoyela et al, 2015).…”
Section: Micronutrient Adequacy In Fortified Food Vehiclessupporting
confidence: 61%
See 1 more Smart Citation